EL DOBLE ANÁLISIS EN COMPONENTES PRINCIPALES PARA DATOS CATEGÓRICOS Y SU APLICACIÓN EN UN ESTUDIO DE MIGRACIÓN - Pérez, Raúl Alberto; Lera, Lydia; Boquet, Ana (Revista Colombiana de Estadística, 2006)
We adapted the double principal component analysis (DACP) (Bouroche 1975), developed for the analysis of three-dimensional quantitative data, to categorical data by mean of the Chi-squared distance between rows and columns profile of a contingency table and we carry out an application to a study of internal migration in Cuba.